2016
DOI: 10.1902/jop.2015.150458
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis Awareness Amongst the General Public: A Critical Systematic Review to Identify Gaps of Knowledge

Abstract: The number of available community-based investigations on periodontal knowledge is scarce and restricted to areas with a very high level of human development. Gaps of knowledge exist in every geographic area, with the most relevant issues of low awareness and poor knowledge about the etiology of periodontal diseases and their relation with systemic disorders. These results highlight the need for local, community-based investigations about periodontal knowledge and barriers hampering early diagnosis, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 45 publications
5
34
0
2
Order By: Relevance
“…Layperson's periodontal awareness in our study is low, as 52.9% did not know the mere existence of periodontitis. Although similar results have been reported worldwide, our sample compares unfavorably with similar studies undertaken in Colombia (33.7%), Nigeria (36.75%), or Germany (15.6%) …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Layperson's periodontal awareness in our study is low, as 52.9% did not know the mere existence of periodontitis. Although similar results have been reported worldwide, our sample compares unfavorably with similar studies undertaken in Colombia (33.7%), Nigeria (36.75%), or Germany (15.6%) …”
Section: Discussionsupporting
confidence: 90%
“…In this sense, patients’ periodontal awareness may play a key role in achieving this goal. Unfortunately, periodontal awareness of the general population seems to be low worldwide and important gaps of knowledge have been identified in every community‐based report published so far …”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it is of the utmost importance to increase the patient's ability to recognize PDs' symptomatology and guarantee their diagnosis understanding. This recognition capacity and the consequent valorization of the disease are of particular importance for a positive outcome in the control and treatment of the disease (Karlsson, Lymer, & Hakeberg, ; Varela‐Centelles et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Bearing in mind the reported low level of knowledge of periodontal health elicited by laypersons (Varela‐Centelles et al, ), together with the gaps observed for physicians and nurses (Varela‐Centelles et al, ), and combined with the high prevalence of periodontal disorders (Albandar & Rams, ), dental clinics should be expected to be the cornerstone of patient periodontal education. A pilot study on general dental practitioners found they perceived useful the participation of the entire dental team in educating patients on periodontal risk factors (Raidi, Thornley, & Thornley, ).…”
Section: Introductionmentioning
confidence: 99%